2020
DOI: 10.1108/ejm-02-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

Home culture consumption as ambivalent embodied experience

Abstract: Purpose The consumer acculturation literature argues that reconstituting familiar embodied practices from the culture of origin leads to a comforting sense of home for consumers who move from one cultural context to another. This paper aims to extend this thesis by examining further dimensions in migrant consumers’ experiences of home culture consumption. Design/methodology/approach This paper analyses data gathered through multi-modal depth interviews with Southeast Asian skilled migrants in New Zealand thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 66 publications
(231 reference statements)
0
19
0
Order By: Relevance
“…The findings of this study extend the boundaries of consumer acculturation research by highlighting how communicating with the home country through a social media platform can influence acculturation processes. Whilst previous consumer acculturation studies have limited the home-culture focus to ethnic community perspectives (Cruz and Buchanan-Oliver, 2020;Luedicke, 2015), or restricted the use of social media to the influence of the host society (Li et al, 2019;Mitra and Evansluong, 2019), the findings of this study extend our understanding of the acculturative processes, particularly in relation to the inclusion of the home-country perspective.…”
Section: Theoretical Contributionsmentioning
confidence: 60%
See 3 more Smart Citations
“…The findings of this study extend the boundaries of consumer acculturation research by highlighting how communicating with the home country through a social media platform can influence acculturation processes. Whilst previous consumer acculturation studies have limited the home-culture focus to ethnic community perspectives (Cruz and Buchanan-Oliver, 2020;Luedicke, 2015), or restricted the use of social media to the influence of the host society (Li et al, 2019;Mitra and Evansluong, 2019), the findings of this study extend our understanding of the acculturative processes, particularly in relation to the inclusion of the home-country perspective.…”
Section: Theoretical Contributionsmentioning
confidence: 60%
“…The concept of acculturation in previous research is mostly regarded as an outcome of offline interactions in the context of immigration (Askegaard et al , 2005; Aung et al , 2017; Cappellini and Yen, 2013; Cruz and Buchanan-Oliver, 2020; Lysonski and Durvasula, 2013; Min and Peñaloza, 2019). Two broad approaches to acculturation have been advanced in the literature: assimilationist and postassimilationist (Luedicke, 2011; Sam, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The moderating role of local food brand value signalling Furthermore, studies have revealed that expatriates are frequently on the lookout for the best value when making the decision to purchase food products and brands (Bundy, 2017). At the same time, studies suggest that migrants, (Cruz and Buchanan-Oliver, 2020) and expatriates (Nowicka, 2007), tend to remain mentally connected to their home country. One recent study shows that expatriates use their home country's traits as a point of reference when assessing a host country's products and offerings (Miocevic and Zdravkovic, 2020a).…”
Section: 4mentioning
confidence: 99%